Seroepidemiology of respiratory (group 2) canine coronavirus, canine parainfluenza virus, and Bordetella bronchiseptica infections in urban dogs in a humane shelter and in rural dogs in small communities - Ellis, John (Canadian Veterinary Medical Association, 2011)
This prospective study evaluated seroepidemiologic features of canine respiratory coronavirus (CRCoV), canine parainfluenza virus (CPIV), and Bordetella bronchiseptica infections in dogs in an urban humane shelter and in rural/small community dog populations in western Canada. Seroprevalence of CRCoV and CPIV was low compared with other countries; seroprevalence of B. bronchiseptica was moderate to high in most populations examined. Rural dogs were 0.421 times (P ≤ 0.0001) less likely to be positive for CRCoV than dogs admitted to the shelter. There were no statistical differences in prevalence of antibodies to B. bronchiseptica and CPIV between urban and rural populations. Dogs from Fort Resolution, NWT were significantly (P < 0.05) less likely to have moderate or high antibody titers to the 3 agents than dogs in the shelter. Seroconversion to CRCoV was common in dogs in the shelter, but was not associated (P = 0.18) with respiratory disease. Antibodies to CRCoV, CPIV, or B. bronchiseptica on arrival were not significantly (P > 0.05) associated with disease-sparing after entry into the shelter.